Physiologically‐based pharmacokinetic model predictions of inter‐ethnic differences in imatinib pharmacokinetics and dosing regimens - Adiwidjaja, Jeffry; Gross, Annette S.; Boddy, Alan V.; McLachlan, Andrew J. (British journal of clinical pharmacology, 2022)
Aims This study implements a physiologically‐based pharmacokinetic (PBPK) modelling approach to investigate inter‐ethnic differences in imatinib pharmacokinetics and dosing regimens. Methods A PBPK model of imatinib was built in the Simcyp Simulator (version 17) integrating in vitro drug metabolism and clinical pharmacokinetic data. The model accounts for ethnic differences in body size and abundance of drug‐metabolising enzymes and proteins involved in imatinib disposition. Utility of this model for prediction of imatinib pharmacokinetics was evaluated across different dosing regimens and ethnic groups. The impact of ethnicity on imatinib dosing was then assessed based on the established range of trough concentrations (Css,min). Results The PBPK model of imatinib demonstrated excellent predictive performance in describing pharmacokinetics and the attained Css,min in patients from different ethnic groups, shown by prediction differences that were within 1.25‐fold of the clinically‐reported values in published studies. PBPK simulation suggested a similar dose of imatinib (400–600 mg/d) to achieve the desirable range of Css,min (1000–3200 ng/mL) in populations of European, Japanese and Chinese ancestry. The simulation indicated that patients of African ancestry may benefit from a higher initial dose (600–800 mg/d) to achieve imatinib target concentrations, due to a higher apparent clearance (CL/F) of imatinib compared to other ethnic groups; however, the clinical data to support this are currently limited. Conclusion PBPK simulations highlighted a potential ethnic difference in the recommended initial dose of imatinib between populations of European and African ancestry, but not populations of Chinese and Japanese ancestry.